Gender in Management: A Sociological Perspective - Palmer, Gill; Kandasaami, Tamilselvi (The International Journal of Accounting and Business Society, 1997)
Thispaper starts with an overview of the literature on gender differences in managerial  bahaviour.  Much  of the research  on  management ignores or denies any difference between  genders.  On  the  other hand,  research  on  management style and gender  stereotypes  demonstrates  that  there  are  real  differences  in  culturally approved  communication  and  interpersonal  influence  methods  used  by  men  and women  (Palmer,  1993;  Willis, 1990).  Empirical  findings  from  a  study  on  women small business owners is used to explain androgyny. We review the evidence for the existence of a ’glass ceiling’ causing discrimination against women in management. We then suggest a theoretical framework of the management process which  can be used to analyse the various ways that gender stereotypes impact on the management processes used within management.When  we  talk  about  gender  in  management,  few  people  would  say  that women have made great strides in every walk of life.  Since the  1970s women have succeeded in combining careers with  families and are moving into male-dominated professions such as law, industry and commerce, but are still not well represented in the more senior positions (Grimwood & Popplestone,  1993). In order to explain this phenomenon we will be discussing the sociological constuction of women and men as  genders,  ‘women’  and  ‘men’  and  ‘masculinity’  are  socially  and  culturally produced and vary with the society and the social context (Symons,  1992). For many years,  men  were  able  to  hold  power  at  all  levels  because  they  were  free  of childbearing  and  child  rearing  responsibilities  and  so  available  to  participate  in social and political life.